"Oh! Iben's Here Now, So We Better Behave Properly"—The Production of Class as Morality in Research Encounters - Aamann, Iben Charlotte (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2017)
This article is a study of how class is produced in research encounters as matters of morality. I engage various class perspectives, arguing that class today occurs in subtle ways, being lived as judgments and struggles around moral authorization. I draw on my experiences during six months of ethnographic fieldwork among ethnic Danish middle- and working-class parents when involved in their six-year-old children's start in the final preschool class. In light of my methodological problems with establishing trustful relations with the participants, I argue that I was being interpreted as a judge with a mandate to pass moral judgments on the parents. While this interpretation was common among the participants, they positioned themselves in three radically different ways towards the researcher and "judge": "eager to get a positive judgment," "in the same boat" and "refusing to get judged." This, I argue, reflects contours of class relations in contemporary, neoliberal societies. I also call for acknowledgment of how the power relations embedded in social, qualitative research are often matters of class. Further, I argue that in a broader methodological perspective, we also need to recognize and investigate the classed dimensions of social research to enhance our understanding of the processes involved in qualitative studies.